2009
DOI: 10.1111/j.1468-3148.2008.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Restraint Procedures and Challenging Behaviours in Intellectual Disability: An Analysis of Causative Factors

Abstract: Background Persons with intellectual disability often evince challenging behaviours. Efforts have been underway for some time to develop prosocial or positive skill acquisition treatments to address challenging behaviours. However, physical ⁄ mechanical and chemical restraint is still commonly used in many clinical and community settings. Such interventions may be planned or unplanned and in some cases implemented by staff ⁄ parents with little training. Method Physical ⁄ mechanical and chemical restraint and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…A recent review by Phillips et al (2010) of behaviour support plans developed by DSWs showed that the key elements required of such plans were often omitted. Such omissions suggest that direct care staff rely on reactive strategies, including restrictive interventions, in managing behaviour (Matson & Boisjoli, 2009). Researchers have questioned the continued use of restrictive interventions and other reactive strategies in response to challenging behaviours in light of the strong evidence base to indicate the effectiveness of positive behaviour supports (Carr et al, 2002;Matson & Boisjoli, 2009;Sturmey, 2009).…”
Section: Concerns About the Ability Of Direct Support Workers To Meetmentioning
confidence: 96%
“…A recent review by Phillips et al (2010) of behaviour support plans developed by DSWs showed that the key elements required of such plans were often omitted. Such omissions suggest that direct care staff rely on reactive strategies, including restrictive interventions, in managing behaviour (Matson & Boisjoli, 2009). Researchers have questioned the continued use of restrictive interventions and other reactive strategies in response to challenging behaviours in light of the strong evidence base to indicate the effectiveness of positive behaviour supports (Carr et al, 2002;Matson & Boisjoli, 2009;Sturmey, 2009).…”
Section: Concerns About the Ability Of Direct Support Workers To Meetmentioning
confidence: 96%
“…They are only used in specific isolated circumstances to "decrease the risk or harm to self or others when other behaviourally based methods are not effective" (Matson & Boisjoili, 2009, p. 113). Holden and Gitlesen (2006) and later Matson and Boisjoili (2009) found the prevalence of aggressive behaviour towards others and self injurious behaviour increased significantly for individuals with an intellectual disability and that these behaviours were utilized as "powerful ways to communicate and to control ones environment" (Matson & Boisjoili, 2009, p. 111) both at home and at school.…”
Section: Law and Guidance For Dealing With Challenging And Violent Bementioning
confidence: 99%
“…This raises some serious ethical and legal questions regarding justifiable grounds for restraint. Matson and Boisjoili (2009) emphasise that "staff understanding the parameters of physical restraint is important" (p. 113) to maintain a firm legal footing.…”
Section: Law and Guidance For Dealing With Challenging And Violent Bementioning
confidence: 99%
See 2 more Smart Citations